The Effect of Business Process Reengineering (BPR) and Service Quality with Technology Utilization on Educational Institutional Performance through Stakeholder Satisfaction - Hidayatullah, Deny; Munir, Munir; Sobandi, A.; Furqon, Chairul (Atestasi : Jurnal Ilmiah Akuntansi, 2024)
This study aims to analyze the effect of Business Process Reengineering (BPR) and service quality with the use of technology on the performance of educational institutions at the National University, with stakeholder satisfaction as an intervening variable. The research methodology uses a quantitative approach with data collection through surveys to various stakeholders of the National University, including leaders, lecturers, education personnel, students, and parents, with a total sample of 200 people. The results showed that Business Process Reengineering (BPR) significantly improves educational institutions' performance, reflecting increased operational efficiency, reduced costs, and improved quality of educational services. In addition, the utilization of appropriate and integrated information technology in educational services also shows a significant influence on the performance of educational institutions, as seen in increased student and staff satisfaction and reduced operational time and costs. Implementing BPR also increases stakeholder satisfaction as more efficient processes and better services meet their expectations and needs. Similarly, service quality with effective utilization of information technology increases stakeholder satisfaction through faster service, easy access to information, and simpler administrative processes. This stakeholder satisfaction, in turn, affects the performance of educational institutions as satisfied stakeholders tend to provide more significant support, thus improving the institution's overall performance. Finally, stakeholder satisfaction mediates the relationship between BPR and service quality and technology utilization in educational institutions' performance, indicating that combining BPR and information technology significantly improves institutional performance through increased stakeholder satisfaction.